The casual grid for spanish de-marked causers - París, Luis Alberto; Califa, Martín Iván (2023)
In this presentation we propose a 'causal grid' that decomposed the predicate CAUSE in terms of a feature structure. Distinct value activation patterns in the 'causal grid' are associated with the various causative meanings encoded in different Spanish forms, respectively. In particular, the different morphosyntactic realizations of the Causer and/or the Causee are linked ystematically to different meanings in a way that follows the RRG linking algorithm. In particular, we shall concentrate here on the value activation pattern that corresponds to the causative meaning of the Spanish preposition de "from/of". Concurrently, our proposal suggests a novel decomposition of the meaning of prepositions.
Keywords: Humanidades::Lenguas y Literatura